Birth and Development of the Uruguayan Freemasonry in the Nineteenth Century - Cano Roa, Efraín (2016)
In the absence of historical works on the Uruguayan Freemasonry, this article aims to analyze the origins and institutionalization of the Order in the nineteenth century. To do this, documents from the first national lodges, newspaper articles of the time and numerous works on the history of Freemasonry in the region are reviewed. The main objective is to rescue the institutionalization process that develops Freemasonry in Uruguay by reference to the following questions: How does this process take place? What are the influences of the Uruguayan Freemasonry? What was the relationship between the different lodges?